2019
DOI: 10.18483/ijsci.2126
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Organic Manures for Improved Performance of Waterleaf (Talinum fructicosum (L) Juss.) in the Humid Tropical Rainforest

Abstract: Waterleaf apart from being a source of food provides employment and income to mostly female peasant farmers. Field experiments were conducted to evaluate effects of organic manure types and their combinations on the growth and yield of water leaf in a typical tropical humid rainforest in 2016 and 2017 Cropping seasons. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Treatments included sole poultry manure (PM) at 10 t ha-1 , 10 t ha-1 cow dung (CD), 8 t ha-1 oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The increased use of these resources by farmers would lead to a corresponding and rational increase in the total output of waterleaf produced. Uko et al (2019) have reported a positive relationship between organic manure application and waterleaf output. Also, the farm size utilized by farmers is depicted in stage one (irrational stage) in the classical production surface.…”
Section: Farm Factor Productivitymentioning
confidence: 97%
See 2 more Smart Citations
“…The increased use of these resources by farmers would lead to a corresponding and rational increase in the total output of waterleaf produced. Uko et al (2019) have reported a positive relationship between organic manure application and waterleaf output. Also, the farm size utilized by farmers is depicted in stage one (irrational stage) in the classical production surface.…”
Section: Farm Factor Productivitymentioning
confidence: 97%
“…Due to the competing needs of farm resources by other crop enterprises and high population density, as well as rapid urbanization (Akpan and Ebong, 2021) in the region, optimum efficiency in farm resource management by waterleaf farmers is the key to sustainable production. Currently, waterleaf is an integral part of urban agriculture, and its production has become one of the most highly preferred livelihood activities among unemployed women in the southern region of Nigeria (Udoh and Etim 2008;Nya et al, 2010;Akpan et al, 2010;Uko et al, 2019 andAkpan, 2020). The sustainability of small-scale farm enterprises like waterleaf production is critical and is necessitated by the need to meet the dietary requirement of the teeming consumers and also achieve food selfsufficiency in the southern region (Akpan et al, 2019c andOlugbire et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation